Profiling immunoglobulin repertoires across multiple human tissues using RNA sequencing - Igor Mandric (Nature Portfolio, 2020)
Information on immune receptor repertoire provides important insights on disease progression and therapy development, but can be expensive and time-consuming to obtain. Here the authors report ImReP, a computational method that can extract detailed immune repertoire information from existing tissue-specific RNA sequencing data.